Formulation of toothpaste tablets with ethanolic leaf extract of Eleusine indica - Cabahug, Aeryne Chloe D.R.; Palevino, Franz Arla O.; Pavia, Hilary Grace C.; Ladignon, Ethel Andrea C. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Toothpaste tablets offer the following advantages over traditional toothpastes: controlled fluoride dose delivery, formulation stability, and use of reusable packaging. The inclusion of herbal ingredients that may offer additional benefits, such as antibacterial property, in such formulations also contribute to its market appeal. Eleusine indica is a local Philippine plant with reported antimicrobial activity. Thus, this study aimed to formulate toothpaste tablets containing E. indica ethanolic leaf extract. Milled E. indica leaves were macerated in ethanol, expressed, filtered, and evaporated in vacuo. Phytochemical screening of the extract confirmed the presence of saponins, carbohydrates, cardiac glycosides, alkaloids, flavonoids, tannins, and phenols. Preformulation studies involved antibacterial susceptibility testing of the extract through agar well diffusion assay and the assessment of stability and compatibility of excipients with the extract via thin-layer chromatography. Results showed that E. indica ethanolic leaf extract did not exhibit a zone of inhibition against Staphylococcus aureus (ATCC 29213) and Streptococcus mutans (ATCC 25175). Trial formulations were still performed using the compatible excipients. The best trial formulation met the set product specifications - evaluated through various quality control tests, and was found to be comparable with commercially available toothpaste tablets.
Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, August 2023
Keywords: Toothpaste -- Tablets -- Formulation; Ethanolic leaf extracts -- Eleusine indica